Basic conditioning factors in informal caregivers of chronic patients at home - Ruiz Valencia, Luis Felipe; Gordillo Sierra, Alisson Michelle; Galvis López, Clara Rocío (Revista Cuidarte, 2019)
Introduction: The increase in chronic diseases places informal caregivers at the patient’s home. Caregivers assume multiple responsibilities immersed in a set of variables that Dorothea Orem calls Conditioning Factors. The objective of this study is to describe the Basic Conditioning Factors of informal caregivers who attended a 2011-2015 training program. Materials and Methods: Descriptive cross-sectional study with a sample size of 110 informal caregivers. A form of basic conditioning factors was designed for data collection, considering the internal and external variables proposed by Orem that were adapted to the living conditions of the informal caregivers. Results: Prevalence of adult women, daughters, with a partner, they coexist with the ill person and there is a high perception of support according to Zimet, as well as development and family-system factors, 10-year care on average, total and serious dependence of the person in care according to Barthel, as factors inherent to the ill person’s role. Discussion: Internal and external factors impact the caregivers’ life and may generate self-care deficits and affect their lives, health and well-being in various ways. Conclusions: Identifying basic conditioning factors in the life of caregivers at home allows setting accompanying strategies to be used by nursing professionals and nursing studentsto strengthen the self-care skills of caregivers and promote the quality of life of the person in care.How to cite this article: Ruiz LF, Gordillo AM, Galvis CR. Factores condicionantes básicos en cuidadores informales de pacientes crónicos en el domicilio. Rev Cuid. 2019; 10(3): e608. http://dx.doi.org/10.15649/cuidarte.v10i3.608
Keywords: Self-Care; Caregivers; Skill; Home Care